Harnessing plastic waste for sustainable membrane filtration with trimodal structure through acid-catalyzed oxidation - Junaid Saleem (14670322) (2024)
Polyolefin waste is among the most generated yet least recycled. Despite its potential as a feedstock of superhydrophobic membranes for organic solvent filtration, it remains a challenge to achieve high selectivity and permeability for viscous oils. In this study, we valorized polyolefin waste into trimodal water filtration membranes through acid-catalyzed oxidation and a void inducer. This approach enabled the creation of membranes with exceptional wettability and strength, characterized by a combination of micropores, macrovoids (30–70 µm), and cavities (150–200 µm). The acid-catalyzed oxidation introduced oxygen moieties into the membrane structure, resulting in a reduced water contact angle, improved hydrophilicity, and increased permeability. The micropores facilitated capillary action, macrovoids enabled efficient water passage, and cavities acted as oil reservoirs, for optimal oil–water separation. Various membranes were synthesized using low-density and high-density polyethylene (PE), polypropylene (PP), and their blend. The obtained results were compared with commercial membranes, revealing a flow rate of 43 ml/min, a retention capacity of 261 mg, and an oil removal efficiency ranging from 84–94 %. Furthermore, the membranes exhibited recyclability, demonstrating stability over at least 10 cycles. This hybrid process transforms plastic waste into trimodal water filtration membranes, achieving a balance between superoleophilicity and hydrophilicity. Other Information Published in: Chemical Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cej.2024.150230